Pengaruh Utang Sektor Publik terhadap Pertumbuhan Ekonomi di Indonesia: Pendekatan VECM Periode 2004-2023 - Hanaldo, Hanaldo; Bintoro, Nugroho Suryo (Fakultas Ekonomika dan Bisnis, Universitas Diponegoro, 2025)
This study aims to analyze and provide additional empirical evidence on the long-term impact of public debt and budget deficits on economic growth in Indonesia between 2004 and 2023, using the Vector Error Correction Model (VECM). The simultaneous rise in public debt and budget deficits may lead to a potential long-term threat to economic growth. This study addresses a gap in the literature by examining the interaction among three key variables—public debt, budget deficits, and economic growth—over the long term (2004–2023) through the VAR-VECM approach, utilizing the most recent data available up to 2023. Using Indonesia’s time-series data from 2004 to 2023 as the study population, the analysis demonstrates a significant impact of public debt on economic growth, thereby confirming the proposed hypothesis. These findings highlight important policy implications, particularly the need to control public debt as a key factor in sustaining long-term economic growth.